Accompanied voices : poets on composers from Thomas Tallis to Arvo Pärt - Greening, John (Boydell Press, 2015)
Accompanied Voices is a unique book: not only is it a highly readable anthology of some of the most memorable and accessible international writing about classical music, and a moving commentary by one set of practising artists on the work of another.